2011
DOI: 10.1007/s12272-011-0820-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of secretory leukocyte protease inhibitor (SLPI) in estradiol valerate (EV) induced polycystic ovary

Abstract: The excessive administration of estradiol valerate induces polycystic ovary syndrome by formation of follicular cysts. Secretory leukocyte protease inhibitor (SLPI) promotes wound healing by decreasing the excessive inflammatory response, stimulating keratinocyte proliferation and increasing collagen deposition through the inhibition of protease activity. In this study, SLPI expression was high in the ovarian stroma, corpus luteum, unilaminar primary follicle, multilaminar primary follicle and granulose layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…In this study, delayed healing in PCOS rat skin wound is consistent with the results showing a large wound area, slow re-epithelization, increased inflammation and matrix degradation. Interestingly, SLPI mRNA and protein expression was higher in the PCOS rat skin than the normal rat skin, and also increased in the PCOS group after wounding, which is consistent with our previous results of SLPI induction in a polycystic ovary (4). Recently, microarray and qPCR data for estrogen-regulated gene expression in old and young human subjects demonstrated that SLPI expression is higher in old human skin than in young human normal skin, which is consistent with the present result (27) and the unpublished results for SLPI expression in OVX mouse normal skin (data not shown).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, delayed healing in PCOS rat skin wound is consistent with the results showing a large wound area, slow re-epithelization, increased inflammation and matrix degradation. Interestingly, SLPI mRNA and protein expression was higher in the PCOS rat skin than the normal rat skin, and also increased in the PCOS group after wounding, which is consistent with our previous results of SLPI induction in a polycystic ovary (4). Recently, microarray and qPCR data for estrogen-regulated gene expression in old and young human subjects demonstrated that SLPI expression is higher in old human skin than in young human normal skin, which is consistent with the present result (27) and the unpublished results for SLPI expression in OVX mouse normal skin (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…The antral-follicle, which produces androgen, is frequently observed in the PCOS ovary instead of the dominant preovulatory follicles (2)(3)(4). PCOS is a hormonal imbalance condition that affects the endocrine system and gives rise to complications, such as obesity and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, SLPI is an anti-inflammatory mediator ( 41 ). SLPI can contribute to wound healing by decreasing the excessive inflammatory response, elevating keratinocyte proliferation and increasing collagen deposition by suppressing the activity of protease ( 42 ). To the best of our knowledge, the association between SLPI and PMOP has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that poly (I:C) increases the secretion of a wide range of antimicrobials and cytokines beyond those measured by us. Other known anti-HIV proteins such as SLPI and cathelicidin are expressed in the ovary [46, 47] and restrict HIV infection at other sites [4850]. Therefore, the increased anti-HIV response could also be due to additional secreted antimicrobials and cytokines.…”
Section: Discussionmentioning
confidence: 99%